Digitalisasi Sistem Keuangan dan Informasi Berbasis Android di RT 05 Karangsari, Sendangtirto, Berbah, Sleman - Peryanto, Ari; Susanto, Dwi; Widodo, Yuwono Fitri; Aditya, Anggie Yudistira (LPPM Universitas Harapan Bangsa Purwokerto, 2025)
Some issues in the neighborhood RT (community association) do not arise without reason. So far, the RT management has not received adequate attention from the local government. The challenges faced by RT administrators in carrying out their duties often conflict with their personal responsibilities as heads of families who need to earn a living, so services to the community can only be provided in the evening or on holidays. The community financial application is designed to address issues in monitoring payment of contributions, difficulties in the contribution collection process, and the management of data that is still done manually, often leading to errors in payment records. With this community financial application, the author hopes that it can make it easier for residents to make contribution payments in a practical and efficient manner, provide monthly financial reports, and remind residents who have not paid through two notifications each month. This application also allows residents to get to know each other through the block menu and helps the administrators in lightening their tasks as well as monitoring the recording and data collection of community contributions.